2020
DOI: 10.1101/2020.10.31.363192
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preserved sensory processing but hampered conflict detection when stimulus input is task-irrelevant

Abstract: Conflict detection in sensory input is central to adaptive human behavior. Perhaps unsurprisingly, past research has shown that conflict may be detected even in the absence of conflict awareness, suggesting that conflict detection is a fully automatic process that does not require attention. Across six behavioral tasks, we manipulated task relevance and response overlap of potentially conflicting stimulus features to test the possibility of conflict processing in the absence of attention. Multivariate analyses… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 123 publications
(186 reference statements)
0
2
0
Order By: Relevance
“…However, behavioral and ERP studies have demonstrated that under some circumstances, unattended information may continue to be processed to relatively high levels of analysis, even when observers are apparently unaware of the information (Volpe et al, 1979;Mangun and Hillyard, 1990;Luck et al, 1996a;Pesciarelli et al, 2007;Codispoti et al, 2016;Sahan et al, 2019). Studies using fMRI have shown that attended visual information can propagate further along the visual processing hierarchy than unattended or ignored information (Marois et al, 2004;Yi et al, 2004;Serences and Boynton, 2007;Cohen et al, 2015;Nuiten et al, 2021;Stein et al, 2021). The temporal dynamics of attended and ignored information processing, however, are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, behavioral and ERP studies have demonstrated that under some circumstances, unattended information may continue to be processed to relatively high levels of analysis, even when observers are apparently unaware of the information (Volpe et al, 1979;Mangun and Hillyard, 1990;Luck et al, 1996a;Pesciarelli et al, 2007;Codispoti et al, 2016;Sahan et al, 2019). Studies using fMRI have shown that attended visual information can propagate further along the visual processing hierarchy than unattended or ignored information (Marois et al, 2004;Yi et al, 2004;Serences and Boynton, 2007;Cohen et al, 2015;Nuiten et al, 2021;Stein et al, 2021). The temporal dynamics of attended and ignored information processing, however, are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Performing high conflict or incongruent trials results in worse performance and longer reaction times compared to low conflict or congruent ones -a behavioral phenomenon known as the congruency effect 10,11 . Previous psychophysical, functional imaging, and electrophysiological studies in humans and non-human primates revealed that fronto-parietal areas are involved in conflict detection and resolution 3,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] . The Conflict Monitoring (CM) model is the most prevalent theory nowadays to explain conflict processing.…”
Section: Introductionmentioning
confidence: 99%